2018
DOI: 10.1111/ctr.13238
|View full text |Cite
|
Sign up to set email alerts
|

Central venous pressure monitoring in living donor kidney recipients does not affect immediate graft function: A propensity score analysis

Abstract: In this single-center analysis, immediate post-transplant renal function was not associated with the use of intraoperative CVP monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A recent study found that CVP does not correlate well with patients’ fluid status neither in general nor during kidney transplantation. 24 Its value as independent risk factor for DGF appears questionable not least because inconsistent results on the ideal range of intraoperative CVP for kidney transplantation were reported. 9,14 Therefore, we focused on the arterial blood pressure as the most frequently used surrogate parameter for organ perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that CVP does not correlate well with patients’ fluid status neither in general nor during kidney transplantation. 24 Its value as independent risk factor for DGF appears questionable not least because inconsistent results on the ideal range of intraoperative CVP for kidney transplantation were reported. 9,14 Therefore, we focused on the arterial blood pressure as the most frequently used surrogate parameter for organ perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a retrospective study of LDKT recipients (100 patients), the authors suggest that a CVP at reperfusion of 12 mm Hg was a factor associated with good early graft function, although the fall in creatinine trends was not significant. 19 Finally, 3 retrospective studies (77 deceased donor transplants recipients, 20 84 out of a cohort of 290 with a CVP measure LDKT, 21 149 patients mixed deceased and LDKT22) found no effect of specific CVP measures on graft outcome. In aggregate, there were no robust data indicating harm with CVP use as a guide if the mean CVP was maintained >5-8 mm Hg without overt fluid overload (CVP > 11 mm Hg), with higher temporary values at the time of reperfusion.…”
Section: Amount Of Fluid Administration and Cvpmentioning
confidence: 99%
“…Pre-load dynamic measurements, such as Pulse-Pressure Variation (PPV) and Sroke-Volume Variation (SVV), can predict fluid responsiveness by analysis of heart-lung interaction triggered by positive pressure ventilation analogously to bedside Frank-Starling curve tests. 6 , 7 …”
mentioning
confidence: 99%